2001
DOI: 10.1007/s007020100017
|View full text |Cite
|
Sign up to set email alerts
|

Suppressed expression of nicotinic acetylcholine receptors by nanomolar β-amyloid peptides in PC12 cells

Abstract: A line of evidence has shown that a link between the common pathological features of beta-amyloid peptide (Abeta) deposition and cholinergic degeneration observed in Alzheimer's disease (AD) may exist, however, no experimental evidence has shown that exposure to Abeta can decrease expression of nicotinic acetylcholine receptors (nAChRs), which have been shown to play roles in brain cognitive functions. Here, we report that treatment with Abeta1-40 and Abeta25-35 at nanomolar concentrations significantly decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
35
0
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 46 publications
6
35
0
2
Order By: Relevance
“…Similar effects of A␤ on nAChR expression have been confirmed in studies using cultured cells; A␤ causes a reduced expression of nAChRs in PC12 cells (Guan et al, 2001), and ␣4, ␣3, and ␣7 expression are all increased in cultured rat astrocytes (Xiu et al, 2005). Thus, AD involves opposite expression level changes in astrocytes compared with neurons, and this might reflect different roles for the same nAChR subunit in different cells, in that ␣7 on glial cells is thought to reduce the intensity of the inflammatory response, whereas it is presumed to have both a fast signaling role and a neuroprotective role in neurons.…”
supporting
confidence: 71%
“…Similar effects of A␤ on nAChR expression have been confirmed in studies using cultured cells; A␤ causes a reduced expression of nAChRs in PC12 cells (Guan et al, 2001), and ␣4, ␣3, and ␣7 expression are all increased in cultured rat astrocytes (Xiu et al, 2005). Thus, AD involves opposite expression level changes in astrocytes compared with neurons, and this might reflect different roles for the same nAChR subunit in different cells, in that ␣7 on glial cells is thought to reduce the intensity of the inflammatory response, whereas it is presumed to have both a fast signaling role and a neuroprotective role in neurons.…”
supporting
confidence: 71%
“…Harkany et al (1998) have shown that bilateral injection of Ab [Phe(SO 3 H) 24 ] 25À35 peptide, a metabolically stable analog of Ab 25À35 , into the rat nucleus basalis magnocellularis causes a reduction of cortical acetylcholinesterase-positive projections. In PC12 cells, Ab has been found to suppress the expression of nAChRs, such as the decrease of nAChRbinding sites, subunit proteins, and mRNA levels (Guan et al, 2001(Guan et al, , 2003. In the present study, in vivo microdialysis experiment revealed that the basal extracellular level of dopamine in the hippocampus of Ab 25À35 -injected mice was decreased compared to that of saline-injected mice.…”
Section: Discussionsupporting
confidence: 51%
“…The aforementioned findings taken together with reports that: (i) A␤ peptides acting via ␣7 nAChRs activate the mitogen-activated protein kinase cascade that plays a critical role in neuronal survival and plasticity in the brain (Dineley et al, 2002), (ii) the ␣7 nAChR activity increases intracellular accumulation of A␤ in neurons (Nagele et al, 2002), and (iii) A␤ peptides downregulate the expression of nAChRs (Guan et al, 2001) indicate that reciprocal relationships might exist in vivo between endogenous levels of A␤ peptide and nAChR activity and may significantly contribute to the pathophysiology of AD.…”
Section: Steroid Hormones and Neuronal Nachrsmentioning
confidence: 73%